Aplikasi Running Text Berupa Jadwal Sholat 5 Waktu Pada Musholla Polman Negeri Bangka Belitung - Aan Febriansyah; Iskandar Iskandar; Bayu Cahyawan; Dian Kusuma Negara (Politeknik Manufaktur Negeri Bangka Belitung, 2016)
In Islam, prayer is an obligation that must be carried out by any of its adherents who already qualified. In one day and one night there are five time prayers, namely Isya, Dawn, Noon, Asr and Maghrib. One of the greatest deeds reward is prayer in congregation at mosques or mosque at the time it was signed in prayer. Usually several mosques or mosque own marker arrival time of prayer are created automatically, making it easier for the muezzin to call the adhan. However it was still a small fraction. There are still many mosques or mosques who do not have means of automatic prayer time this marker. For that know the times of prayer 5 times a day is very important for any religion in the Islamic prayer run the 5 time period with a precise and well. To that end pointer prayer schedule is very important that there. So now many mosques or in homes that are usually already contained a calendar and prayer time enduring performer, but it looks very small so it cannot be seen from a distance. Based on that experience and the importance of this, the authors do make the viewer prayer time in real time that can change with the change of the day, and can be seen from a considerable distance. So that it can function more optimally and can maximize the time available.